Internet Of Things (IOT) For Inventory And Container Position. (July 2020) - Darmawan, C D P; F Dwi, S; Triyasa, D H; Octaviani, R D
Abstract: Along with the rapid development of information technology, there is a change in every field, one of which is in the container depot (container storage). Smooth flow is part of the supporting aspects of the rapid transfer of products to consumers. Internet of Things (IoT) as technological development is a solution to support activities in container depots. The use of an IoT / RFID based system for transporting containers is an indispensable change in the interaction of the smooth flow of container transfers. The containers that are piled up will make the container search process longer and other processes hampered. The author tries to find out how to implement IoT in the depot container to achieve a container depot that is integrated with Information Technology (IT). This research was carried out using a qualitative method that wanted to be seen clearly and deeply what had been done.